Nanopore sequencing from extraction-free direct PCR of dried serum spots for portable hepatitis B virus drug-resistance typing - Astbury, Stuart; Nunes Soares, Marcia Maria Costa; Peprah, Emmanuel; King, Barnabas; Gomes Jardim, Ana Carolina [UNESP]; Farinha Shimizu, Jacqueline [UNESP]; Jalal, Paywast; Saeed, Chiman H.; Sabeer, Furat T.; Irving, William L.; Tarr, Alexander W.; McClure, C. Patrick (Elsevier B.V., 2020)
Background: Effective drug regimens for the treatment of hepatitis B virus (HBV) infections are essential to achieve the World Health Organisation commitment to eliminate viral hepatitis by 2030. Lamivudine (3TC) is widely used in countries with high levels of chronic HBV, however resistance has been shown to occur in up to 50 % of individuals receiving continuous monotherapy for 4 years. Telbivudine (LdT) is now more commonly used in place of lamivudine but is ineffective against 3TC-resistant HBV. Genotyping and identification of resistance-associated substitutions (RAS) is not practical in many locations. Objectives: A novel assay was designed to enable HBV genotyping and characterisation of resistance mutations directly from serum samples stored on filter paper, using Sanger and MinION sequencing. Study design: The assay was applied to a cohort of 30 samples stored on filter paper for several years with HBV viral loads ranging from 8.2 x 10(8) to 635 IU/mL. A set of 6 high-titre samples were used in a proof-of-principle study using the MinION sequencer. Results: The assay allowed determination of HBV genotype and elucidation of RAS down to 600 IU/mL using a 550bp amplicon. Sequencing of a 1.2 kb amplicon using a MinION sequencer gave results consistent with Sanger sequencing and allowed the identification of minor populations of variants. Conclusions: We present two approaches for reliable HBV sequencing and RAS identification using methods suitable for resource-limited environments. This is the first demonstration of extraction-free DNA sequencing direct from DSS using MinION and these workflows are adaptable to the investigation of other DNA viruses.
Keywords: Dried blood spot; Nanopore sequencing; Portable diagnostic test; Hepatitis B virus; Resistance-associated substitutions; Genotyping